Thinking with Witches and Cannibals: The Anthropofagous Sabbat in Europe and America during the Apogee of Witchcraft Trials: Pensando com bruxas e canibais: o sabbat de antropófagos na Europa e América durante o apogeu da repressão judicial à bruxaria - Campagne, Fabián (Revista de Historia Social y de las Mentalidades, 2026)
During the 15th century, radical demonology made cannibalism one of the main features of the Renaissance witch. By the early 16th century, the association between cannibalism, sabbats, and demonolatry was fully established in the European imagination. But at that time, a new phenomenon was beginning in the Americas: the creation of an alternative cannibal myth centered on Indigenous peoples, particularly those settled in the Caribbean islands and on the southeastern coast of Brazil. The mythology surrounding the Brazilian cannibal is particularly relevant because its greatest development occurred precisely during the middle decades of the 16th century, when the legal repression of witchcraft slowed significantly in Europe. However, from the 1570s and 1580s onward, witch-hunts returned with unprecedented vigor in the Old World, thus opening the door to the convergence of the myths of the cannibalistic witch and the Amerindian cannibal. This phenomenon of exchange and hybridization is the historical problem addressed in this article, based on a documentary corpus — chronicles, demonologies and iconography — that will allow us to reconstruct the intense process of cultural circularity that took place at that time around the disturbing practice of anthropophagy.